2017
DOI: 10.1007/s11626-017-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-221 modulates skeletal muscle satellite cells proliferation and differentiation

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNA molecules, which play important roles in animals by targeting mRNA transcripts for translational repression. Many recent studies have shown that miRNAs are involved in the control of muscle development. In this study, the expression levels of miR-221 in different tissues and during rabbit skeletal muscle satellite cells (SMSCs) differentiation were detected. Gene ontology term enrichment was used to predict the potential biological roles of miR-221. A synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In swine, overexpression of miR-143 could induce the increase of slow fibers through targeting the HDAC4 expression 40 . Also, we found some DEMs identified here that involving muscle cell differentiation and energy metabolisms, such as gga-miR-221, gga-miR-34a and gga-miR-126 [41][42][43] . Moreover, the biological functions of a few miRNAs in chicken muscles was revealed through the GO and pathway analysis of intersection genes.…”
Section: Discussionmentioning
confidence: 55%
“…In swine, overexpression of miR-143 could induce the increase of slow fibers through targeting the HDAC4 expression 40 . Also, we found some DEMs identified here that involving muscle cell differentiation and energy metabolisms, such as gga-miR-221, gga-miR-34a and gga-miR-126 [41][42][43] . Moreover, the biological functions of a few miRNAs in chicken muscles was revealed through the GO and pathway analysis of intersection genes.…”
Section: Discussionmentioning
confidence: 55%
“…Combined with the negative effect of miR-186 on rat BMSC osteogenesis and the inhibitory action on the final myogenesis differentiation step by influencing myogenin translation, we deduce that miR-186 may be the driving factor in bone-muscle crosstalk during aging (Antoniou et al, 2014;. Furthermore, the increased miR-221 in aged-BMSC may also function in osteosarcopenia, because it was reported that ectopic overexpression of miR-221 in skeletal muscle satellite cells inhibits myotube formation and miR-221 was found to be a negative regulator of bone formation (Zhang et al, 2017;Liu B. et al, 2018;Gan et al, 2020). Xu R. et al (2018) reported aged BMSCs express high levels of miR-31a-5p leading to bias lineage fate of BMSCs to adipocytes through AT-rich sequence binding protein 2 (SATB2), aged BMSCs also release miR-31a-5p enriched EVs to its microenvironment, inducing increase in osteoclast number and function via the RhoA pathway.…”
Section: Ev-micrornas Of Bone Cells Engaged In Bone-muscle Crosstalkmentioning
confidence: 79%
“…Previous studies had confirmed that miRNA-29 could target Akt3 to reduce proliferation and facilitate differentiation of myoblasts in skeletal muscle development [ 38 ], and miR-26 inhibits expression of Ezh2, a known suppressor of skeletal muscle cell differentiation [ 39 ]. To our knowledge, overexpression of miR-27a in chronic kidney disease mice attenuated muscle loss, improved grip strength [ 40 ], and miR-221 increased skeletal muscle satellite cells proliferation and decreased differentiation [ 41 ]. miR-133 involved in the formation of myotubes and myoblast proliferation [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%